Tafsir Nilai-Nilai Transendensi dalam Al-Qur'an : Kajian Tafsir Ibnu Katsir Terhadap Q.S. Maryam Ayat 1-37 - Sutrisno, Ahmad Dwi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
For a Muslim, faith determines the acceptance or rejection of one's worship and deeds. The concept of faith in the prophetic social sciences initiated by Kuntowijoyo occupies a fundamental position known as transcendence. Transcendence seeks to integrate religious values into the process of constructing civilization. Muslims use the Qur'an and the interpreters' explanations when applying their faith. One of these translators is Ibn Kathir. This study examines how Ibn Kathir views transcendence's importance in Q.S. Maryam: 1-37. This study purpose is to knowing the significance of transcendence and outline Ibn Kathir's analysis of it in Q.S. Maryam: 1-37. This kind of research employs an interpretive methodology and is conducted in libraries. The Qur'an and Ibn Kathir's book